Water experiment for assessing vibroacoustic beamforming gain for acoustic leak detection in a sodium-heated steam generator. (1st December 2019) - Kassab, Souha; Michel, Frédéric; Maxit, Laurent
Highlights: A vibroacoustic leak detection system for sodium heated steam generator is studied. An array of accelerometers fixed on the external shell is used for detection. Two types of beamforming treatments are studied to increase the Signal to Noise ratio. A water experiment confirms the efficiency of the MaxSNR treatment. Abstract: A technique based on vibration measurements has been developed to detect water leaking into sodium in view to improving the monitoring of steam generators. Leak-induced vibrations can be masked by background noise. This problem can be overcome by employing a beamforming technique to increase the signal-to-noise ratio (SNR). In order to study the feasibility and efficiency of this technique for the present configuration, experimental investigations were performed on a mock-up composed of a straight cylindrical pipe coupled to a hydraulic circuit by two flanges. A sound emitter introduced in the pipe simulates the source to be detected while the background noise vibrations are controlled by flow speed. Beamforming is applied to the signals measured by an array of accelerometers mounted externally on the pipe. Two different types of beamforming are considered: the conventional (Bartlett) type and an advanced type based on SNR maximization (MaxSNR). After analysing the vibroacoustic behaviour of the mock-up, the article focuses on the efficiency of the two beamforming treatments for narrow and broad bands.